Evaluation of Double Base Propellant Industry Independence, Using SWOT Analysis, Supply Side - Mirad Fahri; Irdam Ahmad; Romie O Bura; Henry Setyanto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Until now, Indonesia is still importing Double Base Propellant (DBP) for the ammunition and rocket industry. It causes the Indonesian Defense Industry to not be independent. On the other hand, DBP raw materials are abundant in Indonesia. Cellulose and Glycerin are produced from plants or micro-organisms that contain lots of fiber and oil. Therefore, the purpose of writing this paper is to build on the above conditions through a Strength, Weakness, Opportunity, and Threat or SWOT analysis. Starting with the search for data references, then followed by the implementation of workshop activities and discussions and in-depth interviews with experts to find the depth of the data and the assessments of these experts. The SWOT analysis findings provide a perspective and map of the relationship between SWOT elements and alternative action plans. Discussions on building strengths, minimizing weaknesses, looking for opportunities, and countering threats, resulted in recommendations for prioritizing the preparation of a roadmap for the independence of the propellant raw material and the raw material industry dedicated to the propellant industry.